Adaptability investigation of water ecological security and socio-ecological resilience in arid inland river basins, China - Xianglong Gao; Chengpeng Lu; Qi Feng; Wei Liu; Jutao Zhang (Environmental and Sustainability Indicators)
To address the complexity of interactions and cumulative evolution between water ecological security and socio-ecological systems, this study explores their co-evolution and adaptation from the human-water perspective. Although previous studies have extensively analyzed water ecological security and its influencing factors, they often focus on single variables or subsystems, neglecting the intricate coupling between water ecological security and socio-ecological systems. Based on adaptability theory, this study integrates the Water Ecological Security Index (WESI) with a comprehensive adaptability evaluation model to systematically assess the spatiotemporal dynamics and adaptive coordination between water ecological security and socio-ecological resilience in arid inland river basins from 2011 to 2021. The results reveal a gradual improvement in the adaptation between water ecological security and socio-ecological resilience, particularly in the river basins of Xinjiang, where highly adaptation areas have continuously expanded. However, significant disparities in adaptation levels exist across sub-basins, highlighting the need to further promote water-saving irrigation technologies and explore pathways for compact urban development in specific regions. In the future, water resource management in arid inland basins should be guided by the concept of coupled socio-ecological systems, aiming to optimize management frameworks, implement zonal water resource governance, and foster the coordinated advancement of socioeconomic development and ecological conservation.